ANALISIS LAPORAN KEUANGAN UNTUK MEMPREDIKSI POTENSI TERJADI FINANCIAL DISTRESS DENGAN MENGGUNAKAN MODEL SPRINGATE: (STUDI KASUS) PADA PT. ASTRA INTERNATIONAL TBK YANG TERDAFTAR DIBURSA EFEK INDONESIA - Thorman Lumbanraja (Sekolah Tinggi Ilmu Ekonomi Surya Nusantara, 2023)
ABSTRAK This study aims to determine the level of financial distress by using the springate method at PT. Astra International, Tbk. The method used in this research is descriptive method and the data collected is financial report data in 2010-2016 to predict the potential for financial distress. This study uses a quantitative research type and the data source in this study is secondary data in the form of the company's annual financial reports. The data collection technique in this study was the documentation method using data from www.idx.go.id. Variable measurement is done by analyzing the company's financial statements and the data analysis method used in this study is springate ratio analysis. From the results of research using the springate analysis method, it shows that it is likely that the company will experience financial distress in the future when viewed from the results of the analysis of the financial statements of PT. Astra International, Tbk.From the results of the prediction of financial distress in PT. Astra International, Tbk has not experienced any financial distress, and this company is still in good health or not bankrupt, but if it is not handled quickly, it is likely to experience financial distress because the value decreases each year.Keywords: Financial Statements, Financial Distress, Springate